Педагог і його полікультурна освіта - Васянович, Григорій (Видавництво Львівської політехніки, 2013)
В статье анализируется сущность понятия “поликультурное образование педагога”. Обосновывается положение, согласно которого поликультурное образование базируется на основе взаимодействия и взаимообогащения, диалога культур. Характеризуются объективные и субъективные причины, которые препятствуют педагогу приобретать знания на уровне как этничности, так и поликультурности. The article analyses the essence of the notion of “polycultural education of a teacher”. The concept according to which polycultural education is based on the principles of interaction, mutual enrichment, and dialogue of cultures is under consideration. The author characterizes objective and subjective reasons for preventing a teacher from obtaining knowledge on the both levels of ethnicity and polyculture.
Педагог и его поликультурное образование
Teacher and his/her polycultural education
Keywords: личность; педагог; образование; культура; диалог культур; свобода; personality; teacher; education; culture; dialogue of cultures; freedom